KOMPETITIF BISNIS KERAJINAN BUBUT KAYU (Studi kasus di Industri Kerajinan bubut kayu di desa Simo) - Saifudin, Muh. Chusnul (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2017)
This research is to understand: (1). How is the Production Development Effort of wood lathe industry in simo village? (2). What is the Strategy by wood lathe in Simo village in Developing Business Competitively? To achieve the research objectives, the approach used in this study is a qualitative approach. Trying to find out about Competitive Business of woodcraft lathe (Case Study: Production Innovation and Marketing Development of wood lathe handicraft in simo village). The data source of this research is wooden lathes in simo village. The method applied in this research includes qualitative descriptive and research type using case study. The findings of this research indicate that; (1). The effort of handicraft industry of wood lathe in simo village in developing the production: a. Upon the craft of wood lathe makers in Simo village to develop wood bubble production, the Planning Process has developed a production innovation involving a number of stages called Generation ideas. b. Government efforts always provide learning motivation wooden lathe, and provide a cost benefit for each wooden craftsman. c. Attempt to place employees according to their field. (2). Business Development Strategy: a. This lathe industry strategy expands the segment. b. strategy to develop business by conducting coaching on workers, employee performance motivation training, checking facilities and infrastructure, employee performance appraisal, and evaluation.